(untitled) (Mustansiria Dental Journal, 2022)
Aim of the study: The preforming study tended to point the using close reduction Inter maxillary fixation (CRIMF) as definite treatment for comminuted fracture of the mandible under certain conditions for managing same types of mandibular fractures with the evaluating and comparing the outcome and complications between two techniques. Materials and methods: (CRIMF) and (ORIF). A total of 51 patients with comminuted mandibular fractures, aged between (17-45) years. All patients were examined clinically, radio graphically (OPG) and some of them computed tomographically (CT3D) before and after treatment to evaluate the regions fracture position, and assessed the complication resulted post operatively. Patients were divided into 2 groups: Group A (n=30) patients with 36 fractures had managed by close reduction and indirect fixation using intra maxillary fixation (CRIMF). Group B (n= 21) patients with 24 fractures operated by open reduction internal fixation (ORIF) using reconstruction plates. Group A managed by maxilla mandibular fixation MMF were performed for 28 cases under general an anesthesia (GA) and only 2 patients fixed under local anesthesia. In the group B, all surgical operations of ORIF were done under GA.